Analysis and Description of Ancient Sources of Speech Culture - Hikmatxon Ahmedova (Journal of Advanced Zoology, 2023)
The article reflects on the essence of examples of folk oral creativity in speech etiquette and culture, such as short, capacious, shallow, clear, meaningful, meaningful, logical, truthful, effective speech.